UNVEILING THE FUTURE OF DATA EXTRACTION USING PYTHON AND AI FOR VIDEO-BASED INFORMATION RECOGNITION (American Journal of Technology and Applied Sciences, 2023)
In today's data-driven world, the ability to extract valuable information from diverse sources is paramount. This article explores the exciting realm of data extraction from video using Python and Artificial Intelligence (AI). Video-based information recognition has far-reaching applications, from surveillance and marketing to healthcare and education. In this article, we delve into the theory, techniques, and methodologies behind this innovative approach and present promising results that showcase the potential of Python and AI in video data extraction.